The relationship between the Esmeraldas Myths and the development of the reading skill in English for students attending the ninth year of Basic Education at Cristo Rey High School in the city of Esmeraldas, during the second term, 2011-2012 school year - Calderón Centeno, Ligia María (2012)
The present work investigates the deficiencies of reading in English in students attending the ninth year of basic education at Cristo Rey High School in the city of Esmeraldas, during the 2011-2012 school year, for that reason we present as an objective: To determine the relationship between Esmeraldas myths and the development of reading skills in English in students at the Cristo Rey High School, and establish the best strategies for reading in English providing an overview of myths in modern times, analyzing its manifestations in arts and their relationship with the stereotypes in the Esmeraldas students in order to improve their reading and understanding in English. This is a descriptive, quantitative and transversal research because it describes and quantifies the relationship between the Esmeraldas myths and the development of reading skills in English, it is also a field research because it was carried out directly to students attending the 9th year of basic education at Cristo Rey High School in the city of Esmeraldas, the technique used to collect survey data was considered adequate for this type of research. The major findings indicate that the null hypothesis is accepted: The Esmeraldas myths do not contribute to improving of reading in English in students attending the ninth year of basic education at Cristo Rey High School in the city of Esmeraldas, but also is true that reading of myths, legends, tales and stories of Esmeraldas culture, helps to understand English, it is not a crucial factor for this process; in the same way we could say that myths, legends, tales and stories of Esmeraldas culture translated into English, despite of being a more experiential for students is not the only aspect that contributes to this process; also that while the English reading of myths, legends, tales and stories Esmeralda, promotes culture, It does not make a bailout by itself; finally it is also understood that the reading of myths, legends, tales and stories of Esmeraldas culture, is an exercise that helps the type of intensive reading, but it is not crucial to this process.